2015
DOI: 10.3390/ph8030455
|View full text |Cite
|
Sign up to set email alerts
|

On the Quest of Cellular Functions of PEA-15 and the Therapeutic Opportunities

Abstract: Phosphoprotein enriched in astrocytes, 15 KDa (PEA-15), a ubiquitously expressed small protein in all mammals, is known for decades for its potent interactions with various protein partners along distinct biological pathways. Most notable interacting partners of PEA-15 include extracellular signal-regulated kinase 1 and 2 (ERK1/2) in the mitogen activated protein kinase (MAPK) pathway, the Fas-associated death domain (FADD) protein involving in the formation of the death-inducing signaling complex (DISC), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 91 publications
(144 reference statements)
0
9
0
Order By: Relevance
“…3 B ). The cellular functions of PEA-15 are yet to be fully elucidated, but it has been previously shown that PEA-15 can negatively regulate ERK1/2, the Fas-associated death domain, and phospholipase D1 proteins, indicating that it may have antiapoptotic, antiproliferative, and antiinflammatory properties ( 26 ). Overexpression of BCL2 has also been shown to enhance the therapeutic efficacy of tumor-specific T cells ( 27 ).…”
Section: Resultsmentioning
confidence: 99%
“…3 B ). The cellular functions of PEA-15 are yet to be fully elucidated, but it has been previously shown that PEA-15 can negatively regulate ERK1/2, the Fas-associated death domain, and phospholipase D1 proteins, indicating that it may have antiapoptotic, antiproliferative, and antiinflammatory properties ( 26 ). Overexpression of BCL2 has also been shown to enhance the therapeutic efficacy of tumor-specific T cells ( 27 ).…”
Section: Resultsmentioning
confidence: 99%
“…The reorganization of the helices in DED is modulated by the rearrangement of hydrogen-bonding and electrostatic interactions among the polar and charged residues on the DED surface. This result is significant because it provides structural insight on the importance of phosphorylation homeostasis in affecting cellular processes and cell fate [38].…”
Section: Discussionmentioning
confidence: 99%
“…It is implicated in the dysregulation of many signalling pathways involved in cancer progression and tumorigenesis and it has been described to act as both a tumour suppressor and a tumour promoter, dependent on its phosphorylation status [30][31][32]. The PEA15 gene is amplified in breast cancer, as well as in other cancers [33], and the unphosphorylated form of PEA15 is more potent than the phosphorylated form in suppressing tumorigenicity in breast cancer [34]. While several kinases have been reported to be involved in the phosphorylation of PEA15 including Akt, Ca2+/calmodulin-dependent protein kinase (CaMKII) and AMP-activated protein kinase (AMPK) [35,36], the dephosphorylation of PEA15 is much less understood.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Consistent with these observations, others have reported that the non-phosphorylated form of PEA15 binds to the extracellular signal-regulated kinase 1/2 (ERK1/2), preventing its nuclear accumulation, leading to the inhibition of cell proliferation [30,31]. On the other hand, phosphorylation of PEA15 on Ser116 promotes its binding to Fas-associated death domain protein (FADD) via its DED domain, preventing FADD-mediated activation of caspases and the formation of the death inducing signalling complex (DISC), leading to the inhibition of the extrinsic apoptotic pathway [30,33,47].…”
mentioning
confidence: 99%